Civic ideals : conflicting visions of citizenship in U.S. history - Smith, Rogers M., 1953- (Yale ISPS series., 1997)
Is civic identity in the United States really defined by liberal, democratic political principles? Or is U.S. citizenship the product of multiple traditions - not only liberalism and republicanism but also white supremacy, Anglo-Saxon supremacy, Protestant supremacy, and male supremacy? In this powerful and disturbing book, Rogers Smith traces political struggles over U.S. citizenship laws from the colonial period through the Progressive era and shows that throughout this time, most adults were legally denied access to full citizenship, including political rights, solely because of their race, ethnicity, or gender. Basic conflicts over these denials have driven political development in the U.S., Smith argues. These conflicts are what truly define U.S. civic identity up to this day. Smith concludes that today the United States is in a period of reaction against the egalitarian civic reforms of the last generation, with nativist, racist, and sexist beliefs regaining influence. He suggests ways that proponents of liberal democracy should alter their view of U.S. citizenship in order to combat these developments more effectively.